International Workshop on Strange Quarks in Hadrons, Nuclei and Nuclear Matter Ohio University, 12-13 May 2000 (World Scientific Publishing Co. Pte Ltd., 2000)
"This proceedings volume brings together the contributions of experts from different fields within the nuclear physics community. Topics such as rare kaon decays, astrophysics, relativistic heavy ion collisions, and few-GeV electromagnetic probes are covered. The strange quark plays a vital role in understanding such diverse phenomena as CP violation (article by Lincoln Wolfenstein), the "spin crisis" (article by Brad Filipone), and supernova explosions (article by Chris Fryer). Additional topics of interest are parity violation experiments, strangeness content of the proton, and enhanced strangeness production at CERN and RHIC. This unique blend of recent results, with a focus on the role of the strange quark, shows the prominence of strangeness in nuclear physics over the past 50 years."--Publisher's website